Intestinal metabolites and the risk of autistic spectrum disorder: A two-sample Mendelian randomization study - Liu, Deyang; Bu, Dengyin; Li, Hong; Wang, Qingsong; Ding, Xudong; Fang, Xiaolu (Frontiers in Psychiatry, 2023)
Background Observational studies have reported a strong association between autistic spectrum disorder (ASD) and intestinal metabolites. However, it is unclear whether this correlation is causally or violated by confounding or backward causality. Therefore, this study explored the potential causal relationship between intestinal metabolites and dependent metabolites on ASD. Methods We used a two-sample Mendelian random analysis and selected variants closely related to intestinal flora-dependent metabolites as instrumental variables. MR-Egger, inverse variance weighted (IVW), MR-PRESSO, maximum likelihood, and weighted median were performed to reveal their causal relationships. Ten metabolites were studied, which included trimethylamine-N-oxide, betaine, carnitine, choline, glutamate, kynurenine, phenylalanine, serotonin, tryptophan, and tyrosine. Sensitivity tests were also performed to evaluate the robustness of the MR study. Results The IVW method revealed that serotonin may increase the ASD risk (OR 1.060, 95% CI: 1.006–1.118), while choline could decrease the ASD risk (OR 0.925, 95% CI: 0.868–0.988). However, no definite causality was observed between other intestinal metabolites (e.g., trimethylamine-N-oxide, betaine, and carnitine) with ASD. Additionally, neither the funnel plot nor the MR-Egger test showed horizontal pleiotropy, and the MR-PRESSO test found no outliers. Cochran’s Q test showed no significant heterogeneity among the studies, suggesting the robustness of the study. Conclusion Our study found potential causality from intestinal metabolites on ASD. Clinicians are encouraged to offer preventive measures to such populations.